let
x-------> the number of Lucy's orders
y-------> the number of Sam's orders
z-------> the number of Bob's orders
we know that
----> equation A
-----> equation B
-----> equation C
substitute equation B and C in equation A
![x+(x-8)+3x=72\\ 5x=72+8\\ 5x=80\\x=16\\](https://img.qammunity.org/2019/formulas/mathematics/high-school/nuytqy2wcu1wm7i1v0eu05n5rd45h9pk20.png)
find z
![z=3*16=48](https://img.qammunity.org/2019/formulas/mathematics/high-school/llv6ibcux0lcx0u88u0j2fl7j7r4l6fbwf.png)
find y
![y=x-8------> y=16-8=8](https://img.qammunity.org/2019/formulas/mathematics/high-school/cx0rf27zijbf50ve8ozeybozxubimy581n.png)
therefore
the answer is
the number of Lucy's orders is
![16](https://img.qammunity.org/2019/formulas/mathematics/college/wwg5qsf7wmjndvfnpvzmh3wna3tewe2own.png)
the number of Sam's orders is
![8](https://img.qammunity.org/2019/formulas/mathematics/middle-school/5i6dqwcfbz0psof337psyeyjwjdvnzb8b5.png)
the number of Bob's orders is
![48](https://img.qammunity.org/2019/formulas/mathematics/high-school/603ltfikuxcgegifwj2hjf5s9fuotpj15i.png)